Increased enhancement of the liver adjacent to the gallbladder seen with contrast ultrasound: comparison between acute cholecystitis and non-cholecystitis. Issue 1 (December 2016) - Kawai, Ryousuke; Hata, Jiro; Manabe, Noriaki; Imamura, Hiroshi; Iida, Ai; Koyama, Nobuko; Kusunoki, Hiroaki
Abstract Background This study was performed to evaluate the ability of contrast-enhanced ultrasonography (CEUS) with time-intensity curve analysis to demonstrate an increased enhancement of the liver parenchyma adjacent to the inflamed gallbladder, as seen on contrast-enhanced computed tomography. Methods The Ethics Committee of our institution approved the study protocol (Kawasaki Medical School, registration number 1277). From April to November 2013, 11 consecutive patients with acute cholecystitis and 16 patients without cholecystitis consented to CEUS (Sonazoid™) and were enrolled in this study. The gallbladder and liver were scanned by one gastroenterologist using harmonic imaging with a low mechanical index. The raw imaging data were stored. Another physician, blinded to all clinical information, constructed the time-intensity curve. The major axis of the region of interest (ROI) was set in segment 5 (pericholecystic area), and the control ROI in segment 8 at the same depth. The intensity ratio (IR) was defined as the peak intensity of segment 5 divided by the simultaneous value of segment 8. The characteristics of the patient with and without acute cholecystitis were compared. The correlation between the IR and the presence of acute cholecystitis was analyzed using binomial logistic regression analysis. A receiver operating characteristic (ROC) curve analysis was performed as well. Results The IR was significantly higher in the group with than without acute cholecystitis (p  = 0.006). The IR correlated significantly with the presence of acute gallbladder inflammation (p  = 0.043). The area under the ROC curve was estimated as 0.852 (95 % confidence interval, 0.709–0.995). A cut-off value of 2.72 had a sensitivity of 81.8 % and a specificity of 81.3 %. Conclusions The IR obtained by CEUS with time-intensity curve analysis generally demonstrated increased enhancement of the liver parenchyma adjacent to the inflamed gallbladder.